2003
DOI: 10.1002/anie.200351408
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Step Reduction of dpp‐bian with Sodium Metal: Crystal Structures of the Sodium Salts of the Mono‐, Di‐, Tri‐ and Tetraanions of dpp‐bian

Abstract: One ligand, four anions! Four anionic forms of a single ligand bis[N‐(2,6‐diisopropylphenyl)imino]acenaphthene (dpp‐bian) were isolated on a preparative scale for the first time and unambiguously characterized by single‐crystal X‐ray structure analysis. The ligand, dpp‐bian, may be easily reduced in diethyl ether by sodium metal to give the mono‐, di‐, tri‐, or tetranion (depicted).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(110 citation statements)
references
References 45 publications
5
105
0
Order By: Relevance
“…Furthermore,m agnetism data are consistent with an S = 0g round state arising from weak antiferromagnetic coupling. [6] In summary,i ntramolecular charge redistribution is ap roperty not uncommon amongst metal complexes con-taining electroactive ligands;e arly metal complexes containing the redox-active BIAN ligand are no exception. These data confirm that at low temperatures the complex can be described as [V V (L red )(LC) 2 ] + ,w hich undergoes as pin transition with increasing temperature to become [V IV (LC) 3 ] + .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore,m agnetism data are consistent with an S = 0g round state arising from weak antiferromagnetic coupling. [6] In summary,i ntramolecular charge redistribution is ap roperty not uncommon amongst metal complexes con-taining electroactive ligands;e arly metal complexes containing the redox-active BIAN ligand are no exception. These data confirm that at low temperatures the complex can be described as [V V (L red )(LC) 2 ] + ,w hich undergoes as pin transition with increasing temperature to become [V IV (LC) 3 ] + .…”
Section: Methodsmentioning
confidence: 99%
“…[2] Homoleptic complexes provide ap ath for extracting this information, as their high inherent symmetry facilitates electronic and structure treatments to provide parameters that can simplify analyses of more complex systems. [5] This class of ligands are able to coordinate to metal centers in multiple oxidation states, [6] and are known for electronic flexibility, including IET,w ith main-group, [7] late transition, [8] and f-block metals. [5] This class of ligands are able to coordinate to metal centers in multiple oxidation states, [6] and are known for electronic flexibility, including IET,w ith main-group, [7] late transition, [8] and f-block metals.…”
Section: Redox-active Ligands Represent An Increasingly Attractivementioning
confidence: 99%
See 2 more Smart Citations
“…Single molecule magnets( SMMs) are ac lass of compounds capable of retaining molecular magnetization below ac ertain blockingtemperature T B .Inorder to achieve this behavior,abistable ground state is necessary, combined with ap referably large thermalb arrier preventing the flip of the magnetization. While the effect was first discovered in dm etal compound ("Mn 12 OAc"), [1] in recent years lanthanide ions have increasingly enteredt he focus of research and SMM behavior was observed for compounds featuring only as ingle paramagnetic ion. [2] In contrastt om any dm etal compounds the lanthanide ions feature large orbitalcontributions to the total angular momentum of the unpaired electrons, in particular in the second half of the series (Tb 3 + -Yb 3 + ), where spin-orbit-coupling is additive.…”
Section: Introductionmentioning
confidence: 99%